Factors Affecting User Behavior to E-commerce Processed Food Products of Community Enterprise Groups - Chaipattanamatee, Patcharaporn (Community and Social Development Journal, 2021)
The purposes of the present research were to study factors affecting the behavior of users of e-commerce processed food products of community enterprise groups. The samples were internet service users in Prachuap Khiri Khan Province. The sample size was determined using the cochran formula with a 95% confidence amount 450 people. The tools used were e-commerce websites, processed food products of community enterprise groups and questionnaires. Data were analyzed using basic statistics are frequency distribution, percentage, mean and standard deviation. The results showed that behavior of users of e-commerce processed food products of Community enterprise groups consist of 1) demographic factors. In terms of gender, age, status, education, occupation and income. 2) on the satisfaction level, it was found that the overall picture was at the highest level. average value is 4.61 and standard deviation is 0.10 3) regarding the behavior of purchasing products via website, it is found that most users have knowledge about buying products via website at a moderate level at 46.20% and 4) marketing mix (6Ps) found that users value every aspect is at the highest level, average value is 4.60 and standard deviation is 0.17.The study results shown differences such as demography side and other factors. Therefore, the design and development of e-commerce products of community enterprise groups should consider the factors that affect user behavior such as personal basic information, the user-centered design, arranging promotions etc. To support the achievement on goals of e-commerce website development for community enterprise products and continue to expand to other products categories of community enterprise groups further.